Determination of nickel in daphne tea extract and lake water samples by flame atomic absorption spectrophotometry with a zirconium-coated T-shaped slotted quartz tube-atom trap and photochemical vapor generation sample introduction - Buyukpinar, Cagdas; Yazici, Elif; San, Nevim; Komesli, Okan Tarik; Bakirdere, Sezgin (SPRINGER, 2021)
Nickel determination is important because of its use in many industrial areas and its negative effects on human health. In this study, an ultraviolet-based photochemical vapor generation (UV-PVG) setup was combined with a T-shaped zirconium-coated slotted quartz tube-atom trapping (T-SQT-AT) apparatus to boost the sensitivity of a flame atomic absorption spectrophotometer for nickel determination. Nickel was separated from the sample matrix by converting it into its volatile species prior to online preconcentration by trapping on the zirconium-coated T-SQT inner surface. Analytical performance was maximized by optimizing all variable conditions. The limit of detection (LOD) and limit of quantification (LOQ) were found as 10 and 33 mu g/L, respectively. Daphne tea and lake water samples were analyzed under optimum conditions, and there was no detectable nickel in the samples. For this purpose, spiking experiments were carried out for the samples in order to evaluate the applicability and accuracy of the method. The percent recovery values calculated for the two samples spiked at three different concentrations ranged between 90 and 112%. To our best knowledge, this is the first study in literature where UV-PVG was combined with T-SQT-AT for the determination of nickel in daphne tea and lake water samples prior to FAAS determination.
Keywords: Nickel; Photochemical vapor generation; Quartz tube-atom trap; Atomic absorption spectrometry; Daphne tea; SENSITIVE DETERMINATION; ANTIMONY; LEAD; PRECONCENTRATION; MICROEXTRACTION; SPECTROMETRY; CADMIUM; COBALT; SEPARATION; SELENIUM; Environmental Sciences & Ecology